CHARACTERISTICS OF DERMATOPHYTOSIS PATIENTS AT DERMATOVENEROLOGY CLINIC OF RSUP SANGLAH DENPASAR DURING THE PERIOD OF 2017-2019 - Natih, Sintha Aprillia Gita; Wardhana, Made; Puspawati, Ni Made Dwi; Karmila, IGAA Dwi (E-Jurnal Medika Udayana, 2022)
Dermatophytosis is a desases that caused by dermatofita from the family of arthrodermatacecae. There are six types of dermatofitosis based on the lesi location ; which are tinea korporis, tinea kruris, tinea pedis, tinea kaptisis, tinea unguium, tinea barbae and tinea kapitis. tinea korporis and tinea kruris are the most common happens in the dermatifita deases. This research conduct with a descriptive retrospektif method using secondary data from the patient book registration at dermatovenerology clinic of RSUP Sanglah Denpasar during the period of 2017-2019. the data collection base on the criteria of age, sex, old or new patient, type of dermatophytosis and the type of theraphy. during the researc, 123 data were meet the criteria of age, sex,old or new patient, type of dermatophytosis and the type of therapy. Thus, the data analyzed deskriptifly. the highest percentage obtained are tines corporis (33,6%) age group range 1-14 years old (25,4%) 15-24 years old (25,4%), male (55,0%), old patient (51,6%), combination theraphy (54,1%) Keywords : Dermatophytosis, Tinea, Descriptive